Penggunaan Electronic Health Record (EHR) Dalam Keperawatan Jiwa : Literature Review - Muchtarul Fadhal (Institut Citra Internasional, 2022)
In mental health nursing, disease history data and treatment are indispensable in the provision of nursing care. The difficulty of mental disorder patients to tell their medical history and health status becomes difficult for nurses in data collection, while the data is needed to enforce nursing diagnoses. For that, it takes a standardized documenting with a standard format, accurate and simple. Electronic Health Record (EHR) is one of the documenting technologies that have been well standardized. The goal is to identify research articles on The Use of Electronic Health Record (EHR). The library review method is to analyze scientific articles from 4 databases namely BMC Health Service Research, BMC Medical Information & Decision Making, Ebscohost, and Google Scholar. Research Article inclusion criteria, 2011-2021, English. Obtained 10 journals using PICO formulation. Research article analysis techniques are with a table format containing authors, titles, years, methods (design, sample and analysis), and results. Based on 10 research articles obtained shows that EHR that has been integrated between health services, making access between health services open so that the quality of client care becomes better. All articles show different results.